P-028 WEB colombian multicenter experience (WEB.COM) : clinical and radiological mid- term results in the treatment of intracranial aneurysms. (22nd July 2019) - Pabon, B; Diaz, C; Vargas, O; Mejia, J; Fernandez, J; Almeida, R; Lobelo, N
Abstract : Introduction: Woven EndoBridge (WEB) is a novel device for the treatment of ruptured and unruptured bifurcation aneurysms. To our knowledge none experience in Latin America has been reported. In the present study, we present a multi-center early experience and mid-term follow data for patients treated with WEB. Materials and methods: 32 consecutive patients with 33 intracranial aneurysms underwent endovascular treatment using WEB between March 2016 and February 2019 in four different centers and cities. We retrospectively evaluated the angiographic results at the end of the procedure and at follow-up, technical considerations, the clinical status and complications. Results All attempted cases were treated, but one. Non procedural rupture was recorded. Aneurysm locations were internal carotid artery bifurcation (n=6), middle cerebral artery (n =17), anterior communicating artery (n= 4), Basilar Trunk (n =1) and basilar tip (n= 5). Eight patients were treated in the setting of acute subarachnoid hemorrhage. 1.12 Devices per aneurysm. 32 of 33 cases treated with web without coils. In five cases was necessary additional stenting- 15%. 16/29 with angiographic follow-up, complete occlusion A-B in 15/16. Procedural mean time 17 min. Conclusion This series is at the moment the only, multicenter, Latin American experience of patients treated with WEB. The treatment shows a good safety and efficacy in the endovascular treatment of WNB intracranial aneurysms. Disclosures: B. Pabon: 2; C; Microvention, Medtronic, Stryker. C. Diaz: None. O. Vargas: None. J. Mejia: None. J. Fernandez: None. R. Almeida: 2; C; Microvention. N. Lobelo: None.